CPT-Based Interpretation of Pile Load Tests in Clay-Silt Soil - Prakoso W.A. (Institute of Research and Community Outreach - Petra Christian University, 2011)
Two pile axial load tests were performed in a site in Depok, West Java. The soil of the site is predominantly a silt-clay soil, characterized by seven mechanical cone penetration tests (CPTs). The piles were 5.5 m long and 11.5 m long, 250 mm square piles. The results of the static load tests showed that the ultimate capacities were achieved. The axial load tests were subsequently back-analyzed using an axisymmetric finite element model using PLAXIS. In the back-analyses, the soil modulus and shear strength in the model, using the cone penetration resistance as the reference, were adjusted so that the numerical load-settlement curves matched the actual curves. The results of the back-analyses are then synthesized with the results of the CPTs, and are compared with available design guidelines. Some recommendations are then proposed.